PT Sido Muncul,Tbk as an Alternative Investment in 2019 - Anita Munir, M.Fin (Management and Leadership Study Programme, 2019)
This study aims to analyze the performance of PT. Sido Muncul, Tbk as a consideration to determine the fair price of shares in 2019. PT. Sido Muncul, Tbk has succeeded in penetrating the export market by marketing products to countries such as Malaysia, Singapore, Brunei, Australia, South Korea, Nigeria, Algeria, Hong Kong, the United States, Saudi Arabia, Mongolia and Russia. The research method used in this study is a descriptive study method. In this study the author used secondary data by taking PT Sido Muncul, Tbk Financial Report published from 2013-2018. As the result, the performance appraisal of liquidity ratios as a whole from 2013-2019 considered Liquid, and the Leverage ratios is solvable. Besides, profitability ratios, return on asset, return on equity and profit margin is quite high. EV / EBITDA ratio from 2013-2019 is still below the industry average so it is very possible for companies to pursue industry averages which cause stock prices to rise in the future. The results of this study indicate that companies have strong fundamentals.Keywords: Liquidity, Leverage, Profitability and Market Value.